Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Mitochondrial metabolism–associated biomarkers in oral lichen planus and oral squamous cell carcinoma - Qingmei Wang; Fei Lin; Xueying Wang; Weiqun Guan; Weihui Chen (Functional & Integrative Genomics, 2026)

A hypoxia-responsive migrasome-related lncRNA signature predicts prognosis and suggests the MSC-AS1/ITGA5 axis as a potential therapeutic target in head and neck squamous cell carcinoma - Sai Liang; Xin Lin; Fubo Wang; Ming Yang; Gang Qin (Functional & Integrative Genomics, 2026)

DLEU2 promotes the migration and invasion of papillary thyroid carcinoma cells through the ELAVL1/RCC2 axis - Suwei Zuo; Sinuo Sun; Yuanyuan Wang; Jiayin Song; Yanmeng Zhou; Shibo Liu; Gang Xue; Xu Lin; Jing-fang Wu (Functional & Integrative Genomics, 2026)

Retraction Note: Exploring the potential of miR-9a-5p in circadian rhythm and cognitive recovery following brain injury in neonatal rats - Changqin Han; Lin Li; Yajing Yun; Chenxi Feng; Meifang Jin; Xin Ding; Bin Sun; Lixiao Xu (Functional & Integrative Genomics, 2026)

Ferroptosis-related ceRNA axis regulates the apoptosis and proliferation of uveal melanoma cells through MAPRE2 - Hai-Bo Wang; Li Dong; He-Yan Li; Xin Liu; Fan Zhang; Lin-Hui Yuan; Wen-Bin Wei (Functional & Integrative Genomics, 2026)

Bronchial epithelial-derived exosomal SLC6A14 promotes airway inflammation and mucus hypersecretion via the ZFP36L1/IL-8 axis - Yurong Xiao; Yuanhang Jia; Lin Chen (Functional & Integrative Genomics, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Mitochondrial dysfunction in hypertension: mechanistic pathways and therapeutic implications - Jiao Tian; Lin Yi; Yuyuan Lu; Yushun Kou; Lingna Zhang; Penghui Jin; Xiaoke Wang; Tao Wu; Xin Yang; Yiyuan Wang; Ruiling Ma (Functional & Integrative Genomics, 2026)

Whole-genome sequencing and comparative genomics reveal antimicrobial potential and adaptive traits of Bacillus velezensis AM12 - Qianqian Lin; Fengzhi Pan; JinJin Yang; Ruixue pan; Haotian Ma; Shiyun Wu; Mingyuan Jia; Huayuan Xu; Jingchun Wu; Jinju Peng; Yuexia Ding; Fucheng Guo; et al. (Functional & Integrative Genomics, 2026)

Integrating single-cell and bulk RNA-Seq to unravel the molecular mechanisms of airway stenosis - Cheng Xue; Wanyu Wang; Qihong Zhuang; Yihua Lin; Yiming Zeng (Functional & Integrative Genomics, 2026)

The application of RPA-PfAgo technology combined with multidimensional data analysis in the rapid detection of the MTHFR A1298C polymorphism - Yaqun Liu; Lianghui Chen; Xuanyi Zheng; Peikui Yang; Jinkun Han; Jiayi Huang; Yanling Shen; Xiaotong Cai; Miaofen Fang; Yicun Chen; Chengsong Xie; Min Lin; et al. (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

β-Lapachone sensitizes glioblastoma to Temozolomide by inhibiting NF-κB signaling - Chunhua Quan; Ying Liu; Yuan Gao; Houkun Zhou; Haiyan Quan; Anna Han; Xiaodan Lu; Zhenhua Lin (Functional & Integrative Genomics, 2025)

RETRACTED ARTICLE: Exploring the potential of miR-9a-5p in circadian rhythm and cognitive recovery following brain injury in neonatal rats - Changqin Han; Lin Li; Yajing Yun; Chenxi Feng; Meifang Jin; Xin Ding; Bin Sun; Lixiao Xu (Functional & Integrative Genomics, 2025)

Non-coding RNAs-regulated SLC7A11 modulates ferroptosis: a new strategy for cancer therapy - Xinyu Niu; Jiawen Nie; Lijie Zhang; Feng Chen; Zhijuan Lin (Functional & Integrative Genomics, 2025)

Aerococcus christensenii: an emerging pathogen associated with infections and bacteremia in pregnancy—genomic insights and pathogenicity evaluation - Yugui Lin; Jialin He; Qiaoliang Zhang; Yanfen Li; Jialong Ke; Chunxiu Lin; Bingyan Yao; Chilun Zhang; Nan Tan (Functional & Integrative Genomics, 2025)

Integrative analysis identifies FERMT3 as a key regulator of metabolic reprogramming in keloid scarring and metabolic syndrome - Qian Lin; Beichen Cai; Feng Dong; Ruonan Ke; Xiuying Shan; Xuejun Ni; Lu Chen; Chuanshu Cai; Biao Wang (Functional & Integrative Genomics, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Comprehensive multi-omics analysis of nucleotide metabolism: elucidating the role and prognostic significance of UCK2 in bladder cancer - Yadong Guo; Ziyou Lin; Wentao Zhang; Haotian Chen; Yuxin Chen; Yongqiang Liu; Zezhi Shan; Shiyu Mao; Xudong Yao (Functional & Integrative Genomics, 2025)

A new perspective on endometriosis: Integrating eQTL mendelian randomization with transcriptomics and single-cell data analyses - Sheng Dou; Yi Wei; Zongyun Lin; Hui Wu; Fenglian Yang; Xuechang Cen; Wenjing Lu; Haimei Qin; Rong Wang; Junli Wang (Functional & Integrative Genomics, 2025)
Endometriosis is caused by the migration of endometrial cells to locations outside the uterine lining. Despite the increasing prevalence of endometriosis, there has been limited research on genetic effects, and its molecular mechanisms remain unclear. This study aimed to investigate the mechanisms underlying the development of endometriosis and to identify new genetic targets for endometriosis by integrating data from gene chips, single-cell mapping, and genome-wide association study databases. Using the Gene Expression Omnibus database, we downloaded data on normal endometrium, eutopic endometrium, and ectopic lesion tissues to explore the differentially expressed genes (DEGs) between normal and eutopic endometrium, and between eutopic and ectopic endometrium. Assessment of the relationships between DEGs and endometriosis involved differential expression, expression quantitative trait loci (eQTL), and Mendelian randomization (MR) analyses. Two single-cell atlas datasets were then analyzed to explore the mechanisms underlying disease development and progression. Intersection of MR results with DEGs between normal and eutopic endometrium highlighted 28 candidate biomarker genes (17 upregulated and 11 downregulated). Similarly, we identified two additional candidate biomarker genes by intersecting the DEGs between eutopic and ectopic endometrium with MR results. Among these 30 candidates, further filtering using single-cell datasets revealed that the histamine N-methyltransferase ( HNMT ), coiled-coil domain containing 28 A ( CCDC28A ), fatty acid desaturase 1 ( FADS1 ) and mahogunin ring finger 1 ( MGRN1 ) genes were differentially expressed between the normal and eutopic groups, consistent with transcriptomic and MR results. Our findings suggested that eutopic endometrium exhibits epithelial-mesenchymal transition (EMT). Cell communication analysis focused on ciliated epithelial cells expressing CDH1 and KRT23 revealed that, in the eutopic endometrium, ciliated epithelial cells are strongly correlated and interact with natural killer cells, T cells, and B cells. We identified four novel biomarker genes and found evidence for EMT in the eutopic endometrium. The mechanism of endometriosis progression may be closely related to EMT and changes in the immune microenvironment triggered by damage to ciliated epithelial cells.

Single-cell RNA sequencing revealed changes in the tumor microenvironment induced by radiotherapy for cervical cancer and the molecular mechanism of mast cells in immunosuppression - Lujiadai Xue; Linzhi Gao; Shimin Zhou; Chaofan Yan; Xian Zhang; Wei Lin; Hu Li; Yuan Shen; Xiaoyu Wang (Functional & Integrative Genomics, 2025)

Heterogeneity analysis and prognostic model construction of HPV negative oral squamous cell carcinoma T cells using ScRNA-seq and bulk-RNA analysis - Chunyan Li; Zengbo Lv; Chongxin Li; Shixuan Yang; Feineng Liu; Tengfei Zhang; Lin Wang; Wen Zhang; Ruoyu Deng; Guoyu Xu; Huan Luo; Yinhong Zhao; et al. (Functional & Integrative Genomics, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

Long non-coding RNA MAGEA4-AS1 binding to p53 enhances MK2 signaling pathway and promotes the proliferation and metastasis of oral squamous cell carcinoma - Xiaoxiao Wei; Zhangfu Li; Heng Zheng; Xiaolian Li; Yuntao Lin; Hongyu Yang; Yuehong Shen (Functional & Integrative Genomics, 2024)

Bladder cancer: non-coding RNAs and exosomal non-coding RNAs - Jingang Zhao; Yangyang Ma; Xiaodong Zheng; Zhen Sun; Hongxiang Lin; Chuanjun Du; Jing Cao (Functional & Integrative Genomics, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

SIGMAR1 targets AMPK/ULK1 pathway to inhibit SH-SY5Y cell apoptosis by regulating endoplasmic reticulum stress and autophagy - Min Kong; Zhiheng Chen; Zhiqiang Lin; Ping Yin; Qin Zhao (Functional & Integrative Genomics, 2024)

Ubiquitination-specific protease 7 enhances stemness of hepatocellular carcinoma by stabilizing basic transcription factor 3 - Mingchao Hu; Chengchen Dai; Xieyin Sun; Yinqi Chen; Nuo Xu; Zhaoyi Lin; Shiyu Xu; Chun Cheng; Zhonghua Tan; Saiyan Bian; Wenjie Zheng (Functional & Integrative Genomics, 2024)

The cellular trajectories of tumor-associated macrophages decipher the heterogeneity of pancreatic cancer - Jiajing Lin; Fengchun Lu; Yuwei Wu; Heguang Huang; Yu Pan (Functional & Integrative Genomics, 2023)

Novel insights into molecular signatures and pathogenic cell populations shared by systemic lupus erythematosus and vascular dementia - Jing Chen; Xiao’feng Zhao; Cheng Huang; Jia’xing Lin (Functional & Integrative Genomics, 2023)

Long noncoding RNA LINC00482 silencing sensitizes non-small cell lung cancer cells to cisplatin by downregulating CLASRP via E2F1 - Yanming Lin; Jinmei Li; Shujun Li; Yuting Chen; Yiping Luo; Yongcun Wang; Zhixiong Yang (Functional & Integrative Genomics, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Mitochondria-related lncRNAs: predicting prognosis, tumor microenvironment and treatment response in lung adenocarcinoma - Qianhui Zhou; Jiali Xiong; Yan Gao; Rong Yi; Yuzhu Xu; Quefei Chen; Lin Wang; Ying Chen (Functional & Integrative Genomics, 2023)
Lung cancer is the most common type of malignant tumor that affects people in China and even across the globe, as it exhibits the highest rates of morbidity and mortality. Lung adenocarcinoma (LUAD) is a type of lung cancer with a very high incidence. The purpose of this study was to identify potential biomarkers that could be used to forecast the prognosis and improve the existing therapy options for treating LUAD. Clinical and RNA sequencing data of LUAD patients were retrieved from the TCGA database, while the mitochondria-associated gene sets were acquired from the MITOMAP database. Thereafter, Pearson correlation analysis was carried out to screen mitochondria-associated lncRNAs. Furthermore, univariate Cox and Lasso regression analyses were used for the initial screening of the target lncRNAs for prognostic lncRNAs before they could be incorporated into a multivariate Cox Hazard ratio model. Then, the clinical data, concordance index, Kaplan–Meier (K-M) curves, and the clinically-relevant subjects that were approved by the Characteristic Curves (ROC) were employed for assessing the model's predictive value. Additionally, the differences in immune-related functions and biological pathway enrichment between high- and low-risk LUAD groups were examined. Nomograms were developed to anticipate the OS rates of the patients within 1-, 3-, and 5 years, and the differences in drug sensitivity and immunological checkpoints were compared. In this study, 2175 mitochondria-associated lncRNAs were screened. Univariate, multivariate, and Lasso Cox regression analyses were carried out to select 13 lncRNAs with an independent prognostic significance, and a prognostic model was developed. The OS analysis of the established prognostic prediction model revealed significant variations between the high- and low-risk patients. The AUC-ROC values after 1, 3, and 5 years were seen to be 0.746, 0.692, and 0.726, respectively. The results suggested that the prognostic model riskscore could be used as an independent prognostic factor that differed from the other clinical characteristics. After analyzing the findings of the study, it was noted that both the risk groups showed significant differences in their immune functioning, immunological checkpoint genes, and drug sensitivity. The prognosis of patients with LUAD could be accurately and independently predicted using a risk prediction model that included 13 mitochondria-associated lncRNAs.

Integrated metabolomics and transcriptomics analyses reveal the key genes regulating differential metabolites of longissimus dorsi muscle in castrated South Sichuan black goats (Capra hircus) - Nanchi Zhang; Feng Xu; Li Wang; Quzhe Emu; Yong Wei; Lin Zhang; Yuan Xu; Jingsheng Fan; Yan Sun; Shuobu Shama; Hongyan Zhou; Chunmei Li; et al. (Functional & Integrative Genomics, 2023)

Transcriptomic analysis the mechanisms of anti-osteoporosis of desert-living Cistanche herb in ovariectomized rats of postmenopausal osteoporosis - Shuo Tian; Lin Guo; Yagang Song; Jinxin Miao; Mengfan Peng; Xiaoyan Fang; Ming Bai; Mingsan Miao (Functional & Integrative Genomics, 2023)

Involvement of IGF1 in endoplasmic reticulum stress contributes to cataract formation through regulating Nrf2/NF-κB signaling - Ruiping Peng; Hongmei Lin; Haocheng Zhu; Yi Zhang; Tiancheng Bao; Weili Li; Juan Deng (Functional & Integrative Genomics, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Machine learning-based mRNA signature in early acute myocardial infarction patients: the perspective toward immunological, predictive, and personalized - Hai-Hua Pan; Na Yuan; Ling-Yan He; Jia-Lin Sheng; Hui-Lin Hu; Chang-Lin Zhai (Functional & Integrative Genomics, 2023)

Transcriptome analysis reveals the regulatory effects of Bacillus amyloliquefaciens and Bacillus pumilus on immune and digestive related genes in the spleen of weanling black goats - Nanchi Zhang; Juan Li; Li Wang; Yong Wei; Quzhe Emu; Feng Xu; Lin Zhang (Functional & Integrative Genomics, 2023)

Construction and validation of a bladder cancer risk model based on autophagy-related genes - Chong Shen; Yan Yan; Shaobo Yang; Zejin Wang; Zhouliang Wu; Zhi Li; Zhe Zhang; Yuda Lin; Peng Li; Hailong Hu (Functional & Integrative Genomics, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

Oncogenic GBX2 promotes the malignant behaviors of bladder cancer cells by binding to the ITGA5 promoter and activating its transcription - Yaoyao Xiong; Xiaohang Song; Kudusi; Xiongbing Zu; Minfeng Chen; Wei He; Lin Qi (Functional & Integrative Genomics, 2022)

CircPVT1 facilitates the progression of oral squamous cell carcinoma by regulating miR-143-3p/SLC7A11 axis through MAPK signaling pathway - Shiliang Wang; Wenlu Li; Long Yang; Jianqiao Yuan; Lin Wang; Na Li; Hongyu Zhao (Functional & Integrative Genomics, 2022)

Effects of PAMK on lncRNA, miRNA, and mRNA expression profiles of thymic epithelial cells - Qingru Wu; Bingxin Li; Ying Li; Fenfen Liu; Lin Yang; Yongjiang Ma; Yuan Zhang; Danning Xu; Yugu Li (Functional & Integrative Genomics, 2022)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Characteristics and comparative analysis of Mesona chinensis Benth chloroplast genome reveals DNA barcode regions for species identification - Danfeng Tang; Yang Lin; Fan Wei; Changqian Quan; Kunhua Wei; Yanyan Wei; Zhongquan Cai; Muhammad Haneef Kashif; Jianhua Miao (Functional & Integrative Genomics, 2022)

Upregulated microRNA-210-3p improves sevoflurane-induced protective effect on ventricular remodeling in rats with myocardial infarction by inhibiting ADCY9 - Yahui Wu; Taofu Wang; Liang Qiao; Hongqi Lin (Functional & Integrative Genomics, 2022)

Association of DNA methylation and transcriptome reveals epigenetic etiology of heart failure - Zhongxiao Lin; Jishuo Chang; Xinzhi Li; Jianglin Wang; Xiaodan Wu; Xiaoyan Liu; YiZhun Zhu; Xi-Yong Yu (Functional & Integrative Genomics, 2022)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

ARRDC3 polymorphisms may affect the risk of glioma in Chinese Han - Nan Li; Hangyu Shi; Pengfei Hou; Lu Gao; Yongqiang Shi; Weiyang Mi; Gang Zhang; Ning Wang; Wei Dai; Lin Wei; Tianbo Jin; Yongzhi Shi; et al. (Functional & Integrative Genomics, 2022)

Untargeted metabolomic analysis of urine samples for diagnosis of inherited metabolic disorders - Hao Liu; Jiang Zhu; Qiu Li; Dongjuan Wang; Kexing Wan; Zhaojian Yuan; Juan Zhang; Lin Zou; Xiaoyan He; Jingkun Miao (Functional & Integrative Genomics, 2021)

Evaluation of the differences between biofilm and planktonic Brucella abortus via metabolomics and proteomics - Taishan Tang; Ye Xu; Jianfeng Wang; Xiao Tan; Xiaona Zhao; Ping Zhou; Fande Kong; Changqing Zhu; Chengping Lu; Huixing Lin (Functional & Integrative Genomics, 2021)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Gene expression profiles of HTR8-S/Vneo cells after changes in ABCA1 expression - Chengmao Xie; Xiaohui Cai; Xiaoju Wang; Li Lin; Yan Long; Xin Cui (Functional & Integrative Genomics, 2018)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Systematic analysis and comparison of the PHD-Finger gene family in Chinese pear (Pyrus bretschneideri) and its role in fruit development - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Identification of two novel chicken GPR133 variants and their expression in different tissues - Kai Tian; Qihai Xiao; Xueyou Zhang; Xi Lan; Xiaoling Zhao; Yan Wang; Diyan Li; Huadong Yin; Lin Ye; Qing Zhu (Functional & Integrative Genomics, 2017)

Migration of endophytic diazotroph Azorhizobium caulinodans ORS571 inside wheat (Triticum aestivum L) and its effect on microRNAs - Li Qiu; Qiang Li; Junbiao Zhang; Yongchao Chen; Xiaojun Lin; Chao Sun; Weiling Wang; Huawei Liu; Baohong Zhang (Functional & Integrative Genomics, 2017)

Deep-sequencing transcriptome analysis of field-grown Medicago sativa L. crown buds acclimated to freezing stress - Lili Song; Lin Jiang; Yue Chen; Yongjun Shu; Yan Bai; Changhong Guo (Functional & Integrative Genomics, 2016)

PPARGC1B gene is associated with Kashin-Beck disease in Han Chinese - Yan Wen; Jingcan Hao; Xiao Xiao; Wenyu Wang; Xiong Guo; Weimin Lin; Tielin Yang; Xiaogang Liu; Hui Shen; Lijun Tan; Xiangding Chen; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Type 3 iodothyronine deiodinase in neonatal goats: molecular cloning, expression, localization, and methylation signature - Tao Zhong; Peng-Fei Jin; Wei Zhao; Lin-Jie Wang; Li Li; Hong-Ping Zhang (Functional & Integrative Genomics, 2016)

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea - Haifeng Jia; Cheng Zhang; Tariq Pervaiz; Pengcheng Zhao; Zhongjie Liu; Baoju Wang; Chen Wang; Lin Zhang; Jinggui Fang; Jianpu Qian (Functional & Integrative Genomics, 2016)

Exome sequencing identified FGF12 as a novel candidate gene for Kashin-Beck disease - Feng Zhang; Lanlan Dai; Weimin Lin; Wenyu Wang; Xuanzhu Liu; Jianguo Zhang; Tielin Yang; Xiaogang Liu; Hui Shen; Xiangding Chen; Lijun Tan; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Expression analysis of genes encoding mitogen-activated protein kinases in maize provides a key link between abiotic stress signaling and plant reproduction - Wei Sun; Hao Chen; Juan Wang; Hong Wei Sun; Shu Ke Yang; Ya Lin Sang; Xing Bo Lu; Xiao Hui Xu (Functional & Integrative Genomics, 2015)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Genome-wide analysis of Water-stress-responsive microRNA expression profile in tobacco roots - Fuqiang Yin; Jian Gao; Ming Liu; Cheng Qin; Wenyou Zhang; Aiguo Yang; Mingzhong Xia; Zhiming Zhang; Yaou Shen; Haijian Lin; Chenggang Luo; Guangtang Pan (Functional & Integrative Genomics, 2014)

Expression of a potato antimicrobial peptide SN1 increases resistance to take-all pathogen Gaeumannomyces graminis var. tritici in transgenic wheat - Wei Rong; Lin Qi; Jingfen Wang; Lipu Du; Huijun Xu; Aiyun Wang; Zengyan Zhang (Functional & Integrative Genomics, 2013)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

Cytoplasmic male sterility-regulated novel microRNAs from maize - Yaou Shen; Zhiming Zhang; Haijian Lin; Hailan Liu; Jie Chen; Hua Peng; Moju Cao; Tingzhao Rong; Guangtang Pan (Functional & Integrative Genomics, 2011)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)

A mixture model approach to detecting differentially expressed genes with microarray data - Chap T. Le; Wei Pan; Jizhen Lin (Functional & Integrative Genomics, 2003)